Outcomes and Therapeutic Management of Thyroid Carcinoma - Conzo, Giovanni; Patrone, Renato (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Globally, the impact of differentiated thyroid cancers has significantly increased in the last decade, resulting in growth of public health spending. Many international scientific societies are actively involved in the difficult process of building updated guidelines in response to scientific research, especially in the genetic and immunohistochemistry fields. The watch, wait, and see policy has added a new possibility for patients in selected cases. Considering the recognized international interest in this disease, this Special Issue aims to analyze the most recent acquisitions in terms of the diagnosis and therapy of differentiated thyroid cancer. It will offer the reader an updated point of view of the most illustrious endocrinology and endocrine-surgery international schools.